Postmortem Cardiac Troponin-T levels in Heart Blood as a Marker to Diagnose Acute Myocardial Infarction - P. Vinod Kumar1 , Amudhasaharan, Magendran J2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Sudden death accounts for approximately two-thirds of autopsies in Forensic Medicine. Natural deathwithin 1 hour after the beginning of acute symptoms, is defined as Sudden Cardiac Death. Acute Myocardialinfarction (AMI) is a serious and potentially lethal manifestation of coronary artery disease, affecting morethan 7 million people worldwide each year and was proved to be a cause of sudden death. This studyquantitatively analyzed the heart blood for Cardiac Troponin T (cTnT) levels within 48hours after death &correlated with the histological changes of myocardium